ENTRE MÃES E FILHAS, REPRESENTAÇÃO E GÊNERO: UMA LEITURA DA HISTÓRIA NA HISTÓRIA - Lavorati, Carla (2013)
This research explores the relationship established between Literature and History in the novel`s mother`s mother`s mother and her daughters Maria José Silveira, as well as the fictional representations that give life and voice to the alleged women who participated in the history of the formation of the Brazilian people . The aim is to observe how the Literature becomes a fertile space of representations of the social, whereas (re) creates the imagery of an era. As well, note the critical stance that literary narrative holds in relation to official history. In the grounds of the debate around the dialogue between literature and history, were used reflections of intellectuals such as Michel Foucault, Victor Leonardi, Luiz Costa Lima and Sandra Jatahy Pesavento. To think about the issues surrounding the poetics of the historical novel, resort to arguments about the historiographical metafiction, Linda Hutcheon, and the historical novel mediation of Gilmei Fleck. In reading the representations of women in the novel, we traverse the paths theoretical representation concept developed by Roger Chartier, as well as theories of Gender Studies, using theoretical as Margareth Rago, Joan Scott, Teresa De Lauretis, Michelle Perrot. The goal is to keep the analysis of the novel directed to the representation of women who participated in fiction history of the formation of the Brazilian people, keeping attention to the construction of the subjectivity of women and for brands (de) naturalization of the concept of identity and solid feminine essence. As also strengthen critical position that the novel sets analyzed with the silences of official history